2020
DOI: 10.5334/ijic.5480
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of an Integrated Home Care Model Shaped by the Needs of Patients Discharged from the Emergency Department

Abstract: Introduction: Developing community care models aims to satisfy the needs of patients' in-home care comprehensively. This is crucial to decrease adverse events and prevent rehospitalization. Methods: A cross-sectional study was conducted among 200 emergency department patients (EDPs) and 200 general practice patients (GPPs). The modified version of the Camberwell Assessment of Need Short Appraisal Schedule (CANSAS), the Health Behavior Inventory (HBI), the Generalized Self-Efficacy Scale (GSES), the Patient Sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…On the other hand, there are many advantages for elderly individuals to receive comfortable and safe health services at home, such as reducing the risk of hospital infection and using the hospital’s capacity effectively ( 26 ). When elderly and chronically ill individuals receive safe and high-quality health services at home, costs are reduced, and patient satisfaction increases ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are many advantages for elderly individuals to receive comfortable and safe health services at home, such as reducing the risk of hospital infection and using the hospital’s capacity effectively ( 26 ). When elderly and chronically ill individuals receive safe and high-quality health services at home, costs are reduced, and patient satisfaction increases ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly unmet needs in patients increase the risk of hospitalization threefold compared to patients with high levels of need satisfaction [ 28 ]. Based on studies conducted in 11 highly developed countries, patients with FS were found to have high levels of needs, referred to as high-need patients.…”
Section: Discussionmentioning
confidence: 99%
“…Discharge of patients from the hospital is a critical stage in patient care, especially for older adults because they are more frail or at risk of functional decline. 1,2 Older adults who have mobility limitation, loss of independence, undernutrition, poor compliance for advisable lifestyle, and unstable chronic disease after discharge from hospitals have higher risk for readmission. [3][4][5][6] The readmissions after discharge from hospitals are associated with higher comorbidities including diabetes, cardiovascular disease, chronic kidney disease, and have higher risk mortality compared to those who readmitted, suggesting importance of integrated care after discharge from hospitals to prevent readmission.…”
Section: Introductionmentioning
confidence: 99%